Linkages of smallholders' attitudes with the implementation of principles and criteria RSPO certification independent smallholder forum MRM Jambi Province, Sumatera Indonesia. (October 2019) - Rosyani; Saad, Asmadi; Edison
Abstract: Oil palm plantation industry in Indonesia is growing rapidly. Extensive development took place during 1999-2016. The total plantation area reached 11, 118, 795 hectares by 2016. Some 5, 754, 718 hectares was managed by private companies, 4, 656, 648 hectares by smallholders and 707, 429 hectares by state-owned enterprises. Issues of oil palm plantation that are not environmentally friendly are continuously exposed. Therefore, Forum Petani Swadaya-MRM independent smallholder RSPO has obtained certification, meaning that this research is important to be carried out. Respondents in the study were 82 people. Data were analyzed using non-Parametric Chi-Square statistical tests. Smallholders' attitudes and knowledge are cognitively 47.6%, affective 57.3% and conatively 63.4%. Achievement of RSPO principles and criteria; 1). Commitment to transparency is 69%, 2). Compliance with applicable laws and regulations 84%, 3). Commitment to long-term economic and financial viability 64%, 4). Use of appropriate best practices by plantations and factories 47%, 5). Environmental responsibility and conservation of natural resources and biodiversity 41%, 6). Responsible consideration of employees, and of individuals and communities affected by growers and mills 64%, 7). Responsible development of new plantings 71%, and 8). Commitment to continuous improvement in key areas of activities 82%. The relationship between attitude and implementation of principles and criteria for RSPO certification. From the results of parametric statistical tests using Chi-Square, 3.42 thit > ttable 1.68, the meaning of refusal H0 thank H1 means that there is a significant relationship between attitudes and implementation of RSPO certification principles and criteria, there is a tendency for a positive attitude, the implementation of the RSPO principles and certification is high. The assessment between the attitude and application of the principle and criteria shows the sustainability status for the forum certifications.